Frequency of Pain Intensity and Factors Affecting it after Cesarean Section Using Spinal Anesthesia - Alireza Hoghooghy; Atefeh Ghosouri; Azim Honarmand; Milad Masaeli; Fatemeh Ahmadinia (Archives of Anesthesia and Critical Care)
Background: Postoperative pain is an important public health issue that affects the sensory and emotional experiences of patients. This study aimed to understand the impact of pain management on patients. Methods: The present study was a retrospective cross-sectional study conducted on women over 18 years of age who underwent cesarean section with spinal anesthesia in Shahid Beheshti Hospital of Isfahan. Results: In this study, 250 women with a Mean age of 31.75 years and a Mean pain intensity of 8.15 participated. Postoperative pain was more common in people without underlying disease and obese people had more pain. Intravenous pain relievers such as pethidine and diclofenac suppositories temporarily reduced the pain intensity. Conclusion: This study showed that the pain after cesarean section was significantly influenced by the length of the operation, the type of anesthesia, and painkillers, which require strategies to reduce the pain.